2002
DOI: 10.1111/j.1365-2621.2002.tb10694.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium Chloride‐based Prefreezing Treatments on the Quality Factors of Strawberry Jams

Abstract: Vitamin C contents of pretreated strawberries did not change during 2 mo of freezing, but after jam cooking and storage, the vitamin C contents of all the studied jams decreased dramatically. Jams made from strawberries treated with CaCl 2 and PME in a vacuum had the highest firmness compared to the reference or other pretreated jam strawberries (p , 0.05). According to sensory evaluation of the jams, different prefreezing treatments were shown to have a significant influence on the sensory attributes evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…Procedure of jam making was adapted from Suutarinen et al (2002) with some modifications. Strawberries (Fragaria × ananassa Duch.…”
Section: Formulation Of Strawberry Jamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Procedure of jam making was adapted from Suutarinen et al (2002) with some modifications. Strawberries (Fragaria × ananassa Duch.…”
Section: Formulation Of Strawberry Jamsmentioning
confidence: 99%
“…Withy et al (1993) reported that monomeric pigment concentrations decrease during storage, therefore stability of anthocyanins is markedly influenced by temperature (Markakis 1982). It was also demonstrated that vitamin C content decreases significantly during jam making and storage (Suutarinen et al 2002). García-Viguera et al (1999) studied the effect of cultivar and storage temperature (>20°C) and storage period on quality of strawberry jam.…”
Section: Introductionmentioning
confidence: 99%
“…The second process consisted of pulsing infusion, in which the vacuum was pulled for 300 s, released, and then repeated for another 300 s. In the third process, a temperature gradient infusion method was evaluated. Mango cubes were blanched for 150 s at 100 • C, and immediately submerged in Valencia PME (13)(14)(15)(16) Unit ml −1 ) with and without CaCl 2 ·2H 2 O (100 or 1000 ppm) at 4 • C for 2 h. In all process treatments, water infused mangoes and non-infused mangoes were used as controls. The process treatments were replicated three times.…”
Section: Raw Materials and Process Treatmentmentioning
confidence: 99%
“…13 Infusion of exogenous PME increases firmness of peaches 14 as well as strawberry pieces in jam. 15,16 Although infusion of exogenous PME into blanched fruits improves firmness of some fruits, it is not effective with others. 17 In particular, fruits and vegetables with a skin or tough surface, such as peas, corn, cherries and blueberries, resist infusion.…”
Section: Introductionmentioning
confidence: 99%
“…Such a chelation causes the formation of networks among pectin molecules (the egg box model), stabilizes pectin and increases the firmness of plant tissues. Some of the successful applications of enzymatic firming by use of PME involves, firming of strawberries before jam making and freezing [74,75] and firming of apples, strawberries, and raspberries before pasteurization [73]. Besides commercial PMEs, the in situ PME in the product may also be used for firming of fruits and vegetables.…”
Section: Firming Of Fruits and Vegetables Before Processingmentioning
confidence: 99%